THE EFFECT OF GIVING A COMBINATION OF AVOCADO (PERSEA AMERICANA) AND CHOCOLATE JUICE ON REDUCING DYSMINOREA - Neny Yuli Susanti; Liana Devi Octavia; Lailatul Latifah; Hayatul Rahimah; Jasmiati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Dysmenorrhea is a disorder during menstruation, and it can have an effect that can interfere with daily activities. The prevalence of dysmenorrhea in the world is still very high, 1.8-1069,425 (90%). In Indonesia, it was recorded at 64.25%, in East Java at 71.3%, while based on the results of a preliminary study in XI-grade of SMA Ibrahimy 2 of Sukorejo there was 80% of adolescents experienced dysmenorrhea. To determine whether avocado and chocolate juice reduce dysmenorrhea in XI-grade adolescents of SMA Ibrahimy 2 of Sukorejo. This study applied a quasi-experimental design with a one-group pretest-posttest design and control. Samples were taken using purposive sampling, involving 60 participants (30 in the intervention group and 30 in the control group). Data were analyzed through univariate and bivariate analysis. The prevalence of dysmenorrhea in the intervention and control groups generally showed moderate pain, with 38 cases (63.3%). The Chi-Square test revealed no significant correlation between the three categorical variables with dysmenorrhea because the p-value > 0.05. However, for the age of menarche, the p-value of 0.016 < 0.05 indicated a correlation with the level of dysmenorrhea pain. The results of the Wilcoxon test showed that both groups experienced significant changes, but the changes in the control group were more significant than the intervention group. The Mann-Whitney test with a p-value of 0.000 < 0.05 rejected H0 and accepted Ha, which means that the administration of avocado and chocolate juice significantly affects primary dysmenorrhea. The administration of a combination of avocado and chocolate juice significantly reduces primary dysmenorrhea in XI-grade adolescents at SMA Ibrahimy 2 of Sukorejo.